VARIASI KONSENTRASI GLISEROL PADA PEMBUATAN EDIBLE FILM PATI KULIT PISANG BARANGAN (Musa acuminata Linn.) - Reni Andriani; Farida Hanum Hamzah; Shanti Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Banana peel is an organic waste that has high carbohydrate content such as starch which can be used as a raw material for making edible film. The purpose of this study was to obtain the best glycerol concentration in the manufacture of edible films of barangan banana peel starch (Musa acuminata Linn.). This research was conducted experimentally by using complete randomized design (CRD) which consists of five treatments and three replications, thus analyzed by using analysis of variance (ANOVA) and followed by duncan’s new multiple range test (DNMRT) at level 5%. The treatments in this research were P1 (addition of 1% glycerol), P2 (addition of 2% glycerol), P3 (addition of 3% glycerol), P4 (addition of 4% glycerol), and P5 (addition of 5% glycerol) in formulation of edible films. The observation consists of tensile strength, elongation, thickness, water resistance, solubility, and water vapor transmission rate. The best treatment was P1 which has a tensile strength of 3,32 MPa, elongation of 18,50%, thickness of 0,13 mm, water resistance of 2,75%, solubility of 15,42%, and water vapor transmission rate of 12,63 g,m-2.h. Keywords: Glycerol, edible film, banana peel, starch.